More than a Diagnosis: How Prenatal Identification of Cantú Syndrome Transformed a Family’s Medical Narrative - Narbona-Arias, Isidoro; Blasco Alonso, Marta; Monís-Rodríguez, Susana; Gómez-Muñoz, Cristina; González-Mesa, Ernesto Santiago; Lubián López, Daniel María; Jiménez-López, Jesús Salvador (MDPI, 2025)
Cantú syndrome is a rare autosomal dominant genetic disorder caused by gain-of-function variants in the ABCC9 or KCNJ8 genes. Although its phenotypic expression is variable and can go unnoticed postnatally, certain ultrasound findings may raise suspicion during pregnancy. This article presents a case of prenatal diagnosis through exome sequencing, which also enabled retrospective diagnosis in the mother and a previously undiagnosed child, highlighting the clinical and emotional value of diagnostic certainty in fetal medicine. Methods: We conducted a descriptive observational study based on a case identified at the Fetal Medicine Unit of the Regional University Hospital of Málaga. The patient underwent high-resolution ultrasound and trio-based exome sequencing (fetus and both parents). Results: Prenatal exome sequencing revealed a heterozygous pathogenic variant in ABCC9, consistent with Cantú syndrome, identified simultaneously in the fetus and the mother as part of a trio-based analysis, confirming maternal inheritance. The same variant was later detected in the patient’s older daughter, who had been under pediatric evaluation for a suggestive phenotype but had not received a genetic diagnosis until this study. The prenatal diagnosis allowed for obstetric and neonatal planning, genetic counselling, and a reinterpretation of the clinical and emotional meaning of previous pregnancies. Conclusions: Prenatal diagnosis of Cantú syndrome enables anticipation of perinatal complications, planned clinical interventions, and also provides emotional relief and a coherent narrative for families. In scenarios of variable phenotypic expressivity, fetal medicine may represent a gateway to family diagnosis, with significant clinical and psychosocial implications.
Keywords: Obstetricia; Enfermedades hereditarias; Fetal medicine; Trio exome sequencing; ABCC9 variants; Rare diseases; Variable expressivity; Genetic counseling; Perinatal mental health; Prenatal diagnosis; Prenatal diagnosis